Pengaruh Komposisi Media Tanam Organik Arang Sekam Dan Pupuk Kotoran Sapi Terhadap Pertumbuhan dan Kelangsungan Hidup Tanaman Cabai Merah (Capsicum annum L.) dan Cabai Rawit (Capsicum frutescens L.) - Nuke, Yolanda; Ledheng, Ludgardis; Yustiningsing, Maria (Bioma : Berkala Ilmiah Biologi, 2021)
This study aims to determine the effect of organic growing media composition of husk charcoal and cow dung on the growth and survival of red chili (Capsicum annum L.) and cayenne pepper (Capsicum frutescens L.). The research was conducted in November 2019 – February 2020 in Faennake Village, North Bikomi District, TTU Regency. The method used in this study is an experimental method with a two-factor randomized block design with five treatments and four replications. The first factor is a large red chili plant. The second factor is cayenne pepper plants with different planting media treatments. The parameters studied were plant height, number of leaves, number of fruit, number of productive branches and plant survival of red chili and cayenne pepper. Data were analyzed through ANOVA with an error rate of 0.5% and to determine the difference between treatments using Duncan's multiple range test with a significance level of 5%. The results showed that the survival of red chili and cayenne pepper in each treatment was good because each planting medium was able to meet the needs of these plants. As for the growth in the treatment of 50% soil, 25% husk charcoal, 25% cow dung, it showed a good effect where in red chili plants the plant height at 45 DAP was 59.5 cm. And for cayenne pepper plants at 45 DAP, which is 50.75 cm. From the observations, it can be concluded that the composition of the growing media 50% soil plus 25% husk charcoal and 25% cow manure was able to increase the growth and yield of Capsicum annum L. and Capsicum frutescens L. plants.